2022
DOI: 10.1002/cam4.5097
|View full text |Cite
|
Sign up to set email alerts
|

Radiomic study on preoperative multi‐modal magnetic resonance images identifies IDH‐mutant TERT promoter‐mutant gliomas

Abstract: Objectives Gliomas with comutations of isocitrate dehydrogenase (IDH) genes and telomerase reverse transcriptase (TERT) gene promoter (IDHmut pTERTmut) show distinct biological features and respond to first‐line treatment differently in comparison with other gliomas. This study aimed to characterize the IDHmut pTERTmut gliomas in multimodal MRI using the radiomic method and establish a precise diagnostic model identifying this group of gliomas. Methods A total of 140 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 48 publications
(95 reference statements)
0
11
0
Order By: Relevance
“…Previous studies have only focused on a single radiomics approach to predict TERT promoter mutation status in patients with gliomas 17,28–30 . Few studies have explored whether the stacking fusion method combining radiomics and DL signatures can improve the prediction of TERT promoter mutation status.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have only focused on a single radiomics approach to predict TERT promoter mutation status in patients with gliomas 17,28–30 . Few studies have explored whether the stacking fusion method combining radiomics and DL signatures can improve the prediction of TERT promoter mutation status.…”
Section: Discussionmentioning
confidence: 99%
“…27 Previous studies have only focused on a single radiomics approach to predict TERT promoter mutation status in patients with gliomas. 17,[28][29][30] Few studies have explored whether the stacking fusion method combining radiomics and DL signatures can improve the prediction of TERT promoter mutation status. In a study on glioma grading, Ning et al 19 found that, regardless of whether single-or multimodality MRI was used, the combination of radiomics and DL had better performance than that of radiomics or DL alone, which is consistent with the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have demonstrated that specific radiomic features, including tumor shape, texture, and enhancement patterns, can provide valuable insights for predicting TERT promoter mutations and survival outcomes (Fang et al., 2020 ; Ivanidze et al., 2019 ). More recently, several researchers have employed multi‐parameter MRI radiomics analysis to effectively differentiate TERT mutant gliomas from wild‐type counterparts with promising results (He et al., 2022 ; Park, Han et al., 2021 ; Tian et al., 2020 ; Wang et al., 2023 ). However, these studies have predominantly focused on grade 2–4 gliomas, and there is a limited amount of literature regarding the utilization of radiomics analysis to differentiate TERT promoter status in patients with GBM.…”
Section: Introductionmentioning
confidence: 99%